2017
DOI: 10.1080/13651501.2017.1411516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peripheral serotonin content and α2-adrenergic receptor function as potential markers for life-long recurrent depressive disorder by using methodological improvements

Abstract: The evaluated peripheral markers reflect only state (but not trait) abnormalities in patients with current severe episode of RDD. The observed peripheral α-AR and serotonin abnormalities are mutually not related and they are probably triggered by different mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
2
3
1
Order By: Relevance
“…The analysis of the 5-HT content in platelets and serum showed lower 5-HT contents in patients compared with healthy participants. These findings are in accordance with several previous studies (Aleksovski et al, 2018;Maurer-Spurej et al, 2004) and suggest a dysregulation of the serotonergic system in the peripheral blood of depressed patients.…”
Section: Interaction Of Serotonin and The Immune Systemsupporting
confidence: 94%
“…The analysis of the 5-HT content in platelets and serum showed lower 5-HT contents in patients compared with healthy participants. These findings are in accordance with several previous studies (Aleksovski et al, 2018;Maurer-Spurej et al, 2004) and suggest a dysregulation of the serotonergic system in the peripheral blood of depressed patients.…”
Section: Interaction Of Serotonin and The Immune Systemsupporting
confidence: 94%
“…In recent studies, it has been suggested that there is no difference between platelet 5-HT levels between patients with depressive symptoms and healthy individuals (33,34). Although the findings of our study show that 5-HT levels are affected by familial stressors, they do not provide sufficient evidence.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the content of serotonin in serum and platelets, we detected lower serotonin contents in patients compared to healthy participants. These findings are in line with several previous studies, whereas others revealed no differences in platelet serotonin content between patients suffering from depression and healthy participants [ 9 , 43 , 44 , 45 ]. Concerning the decreased peripheral serotonin concentration in patients compared to healthy controls, it should be considered that the influence of SSRI/SNRIs is reflected in these results.…”
Section: Discussionsupporting
confidence: 93%
“…More investigations are adjuvant to clarify the implication of combining medications in the treatment of depression. Interestingly, Aleksovski and colleagues suggested that the peripheral abnormalities in serotonin content are caused by an altered function of the serotonin transporter [ 43 , 49 ].…”
Section: Discussionmentioning
confidence: 99%